Pendampingan Asesmen Diagnostik dalam Kurikulum Merdeka di SMA Negeri 1 Ba’a Kabupaten Rote Ndao - Koroh, Lanny I. D.; Ali, Umar; Syahputra, Andrian Wira; Leobisa, Jonathan; Lao, Hendrik A.E. (Institut Agama Kristen Negeri Kupang, 2024)
This training is to provide an understanding to principals and teachers about the diagnostic assessment that is currently in effect in the independent curriculum. The targets of this Community Service group activity are principals, educators and education staff at SMA Negeri I Ba'a, Rote Ndao Regency. The activity was carried out for 2 days. The main material presented was to provide education and workshops through mentoring in making diagnostic instruments and providing practice/simulations regarding concrete steps in preparing diagnostic assessments. The method used in implementing the activity was Participatory Action Research (PAR). The PKM activity was applied with lecture activities and strengthened through FGD (Focus Group Discussion) discussions and questions and answers between presenters/stakeholders and participants. The number of participants who took part in the training was 35 teachers. The results of the training showed that the understanding and mastery of the material on writing diagnostic assessment instruments in the independent curriculum had been understood by the participants and produced a draft of the diagnostic assessment instrument and directly practiced concrete steps in preparing all the required documents. The training participants were very enthusiastic in participating in this activity because it was a requirement in the independent curriculum.